Enterprise resource planning adoption and satisfaction determinants - Ferreira, Eurico Edgar de Oliveira Delgado (2016)
Enterprise Resource Planning (ERP) systems are at the core of every firm. Making people use this costly and time consuming investment is one of the most important issues to deal with. The main objective of the present dissertation is to find the key determinants that open the door to user satisfaction and adoption. A theoretical model was set and an online survey was conducted to understand ERP users’ perspective on such matters. The outcome was the model validation and the understanding that top management support, training, and the system quality are important constructs to assess adoption and user satisfaction. In fact, the latter (system quality) has a significant influence on the behavioural intention to use and also in the overall user satisfaction.